Operational Challenges and Maintenance Strategies of Marine Fresh Water Generator System - Filemon Filemon; Junaidi Roni Prastia; Fajar Gumelar; Fadel Muhammad; Meti Kendek (Equivalent: Jurnal Ilmiah Sosial Teknik, 2026)
Background: The Fresh Water Generator (FWG) is a critical shipboard system that produces potable and technical fresh water from seawater via vacuum evaporation, utilizing waste heat from the main engine jacket cooling water circuit.  The FWG is susceptible to operational disruptions including heat exchanger fouling, mineral scaling, vacuum system failures, thermal efficiency reduction, and salinity monitoring errors. Objective: This study investigates these operational challenges and the maintenance strategies employed to address them, based on the direct professional experience of marine engineers employed by Anthony Veder Rederijzaken, a Rotterdam-based LNG shipping company. Methods: A qualitative case study methodology was adopted, using semi-structured interviews with five marine engineers at the rank of Second and Third Engineer. Five respondents were sufficient because thematic data saturation was reached, with no new themes emerging from the final interviews. Interview data were analyzed manually through thematic analysis, supported by technical document review and structured literature comparison. Results: Five operational challenge themes were identified: biofouling and physical fouling of plate heat exchangers; mineral scaling from calcium carbonate and magnesium hydroxide precipitation; vacuum system degradation from air ingress; reduced thermal efficiency under variable engine load; and salinity monitoring system failures. Corresponding maintenance strategies include scheduled chemical descaling, vacuum integrity checks, routine performance monitoring, pump and ejector overhauls, and weekly salinometer calibration. These findings contribute a practitioner-grounded, route-adaptive framework for condition-based maintenance practice. Conclusion:  The findings offer evidence-based recommendations that advance maintenance management in maritime engineering and provide empirical material for strengthening maritime education curricula.